WATER BALANCE IN SUMBER MULYA VILLAGE, MERAUKE REGENCY - Eprosina Jarmida Soumokil; Ulfa Fitriati (Universitas Lambung Mangkurat, 2011)
Sumber Mulya village is part of Rawa Indah Lowland development area that consists of Kaliki - Sumber Mulya - Jaya Makmur unit. Agricultural area in Sumber Mulya Village is currently processed with relatively small production results due to traditional method of cultivation and water shortage problem.Inflow to Rawa Keramati is larger than the existing irrigation water demand. However, it has only small capacity in utilizing inflow that results in a lot of wasted water during the rainy season. By using Standard Operating Rule model, the most optimum capability of the swamp to fulfil irigation water demand under various canges of cultivation pattern and schedule can be identified. Optimum result is determined using an approach on Analytical Hierarchy Process (AHP) model.Swamp operation analysis was carried out to the four cultivation schedule alternatives with 100% swamp realase capacity. Based on Analytical Hierarchy Process (AHP) method used for the four cultivation patterns and schedules alternatives reviewed based on adequacy, effectiveness and efficiency factor, the optimum results was obtained at alternative in November. It showed Rawa Keramati water resource capability in supplying Sumber Mulya village water demand with irrigated areas of ±595 Ha, ±594 Ha, and ±593 Ha for the firstcrop, second-crop, and third-crop season, respectively.